Fixed or Flexible? : Getting the Exchange Rate Right in the 1990s - Aziz, Jahangir (Economic Issues; Economic Issues ;, 1998)
This paper examines the recent evolution of exchange rate policies in the developing world. It looks at why so many countries have made a transition from fixed or "pegged" exchange rates to "managed floating" currencies. It discusses how economics perform under different exchange rate arrangements, issues in the choice of regime, and the challenges poised by a world or increasing capital mobility, especially when banking sectors are inadequately regulated or supervised.